Clinical Features and Surgical Outcomes of Patients With Moyamoya Disease and the Homozygous RNF213 p.R4810K Variant. (November 2019) - Zhang, Qian; Ge, Peicong; Ma, Yonggang; Zhang, Dong; Wang, Rong; Zhang, Yan; Wang, Shuo; Cao, Yong; Zhao, Meng; Zhao, Jizong
The ring-finger protein 213 ( RNF213 ) gene is a major susceptibility gene for moyamoya disease. The homozygote of the p.R4810K variant on RNF213 exhibits an early onset age and severe form of moyamoya disease. We report 4 unrelated pediatric moyamoya disease cases with the homozygous p.R4810K variant and the long-term surgical outcomes. Published reports on surgical outcome of moyamoya disease case with the homozygous p.R4810K variant were reviewed. Cerebral angiography revealed classic angiographic findings of moyamoya disease in 7 hemispheres of the 4 children. All patients underwent successful indirect revascularization. Abundant collateral blood flow from the external carotid arteries to the internal carotid arteries was observed in all bypass procedures by angiography. Improvements in symptoms and cerebral blood volume were observed in all patients at long-term follow-up. This report is the first case series in the literature on the surgical management of these patients. These cases highlight the effectiveness of indirect revascularization for moyamoya disease patients with the homozygous p.R4810K variant. Early diagnosis and treatment are crucial to avoid irreversible neurologic deficits in these patients.